Pet ownership and homelessness: a scoping review. Issue 2 (3rd July 2019) - Kerman, Nick; Gran-Ruaz, Sophia; Lem, Michelle
ABSTRACT: Between 5 and 25% of people experiencing homelessness have pets. Pet ownership can have a range of impacts in the lives of people experiencing homelessness, which may mitigate or further complicate the many adversities they face. However, there is a need to better understand the benefits and challenges associated with pet ownership to determine how this group can be best supported. Accordingly, a scoping review was conducted using PubMed, PsycINFO, and Google Scholar to address the question: What are the effects of pet ownership on people experiencing homelessness? All of the 18 reviewed studies used either qualitative or cross-sectional research designs. Three domains have been principally examined in relation to pet ownership and homelessness: (1) psychological health and purpose; (2) social support and connection; and (3) access to housing, employment, and service use. Physical health, violence, and crime were less frequently studied. Although the findings offer further support that there are both benefits and liabilities to pet ownership for people experiencing homelessness, there is a critical need for more rigorous research, including longitudinal and intervention studies. Recommendations for developing more pet-friendly services and using a strengths-based approach that considers animal companionship when working with people experiencing housing instability are also discussed.